FOSTERING CREATIVE THINKING IN SCHOOL STUDENTS THROUGH HISTORICAL ART: PEDAGOGICAL PERSPECTIVES - Dagarova Shodiya Hayotjon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article investigates the role of historical artworks in fostering creative thinking among school students. It examines pedagogical strategies for engaging learners with historical visual materials and evaluates their effectiveness in promoting imagination, problem-solving, and artistic expression. The study demonstrates that incorporating historical art into classroom activities enhances students’ critical reasoning, emotional intelligence, and aesthetic appreciation. The findings provide practical guidance for educators seeking to implement art-based learning strategies in schools.